Urgensi Pembatasan Masa periode Anggota Dewan Perwakilan Rakyat dalam Upaya Pencegahan Penyalahgunaan Kekuasaan - Khaerunnailla, Wa Ode Fatihatul; Negara, Tunggul Ansari Setia; Madjid, Abdul (Universitas Negeri Malang, 2019)
This paper aims to discuss the authority of members of the House of Representatives (DPR) in the 1945 Constitution of the Republic of Indonesia (UUDNRI 1945), the legal vacuum in determining the tenure of the DPR, and the urgency of ideal regulation DPR tenure. The study uses normative juridical research with a statutory and conceptual approach. The power of the DPR in the 1945 Constitution is very broad, not only relates to legislative power but also the executive and judicial. The regulation regarding the time limit for the DPR’s period has not yet been regulated (there is a legal vacuum). There is no statutory regulation governing the time limit for a person to become a member of the DPR. The urgency of limiting the period of members of the House of Representatives is to limit the holding of power too long and provide opportunities for other citizens. Members of the Regional House of Representative (DPRD) can serve for 2 periods at the district/city level, after which they can submit at the provincial level for 2 periods, and finally can apply to become a member of the DPR RI for 2 periods.